Environmental metagenetics unveil novel plant‐pollinator interactions - Sydney B. Wizenberg; Laura R. Newburn; Rodney T. Richardson; Mateus Pepinelli; Ida M. Conflitti; Mashaba Moubony; Daniel Borges; M. Marta Guarna; Ernesto Guzman‐Novoa; Leonard J. Foster; Amro Zayed (Ecology and Evolution, 2023)
Abstract Honey bees are efficient pollinators of flowering plants, aiding in the plant reproductive cycle and acting as vehicles for evolutionary processes. Their role as agents of selection and drivers of gene flow is instrumental to the structure of plant populations, but historically, our understanding of their influence has been limited to predominantly insect‐dispersed flowering species. Recent metagenetic work has provided evidence that honey bees also forage on pollen from anemophilous species, suggesting that their role as vectors for transmission of plant genetic material is not confined to groups designated as entomophilous, and leading us to ask: could honey bees act as dispersal agents for non‐flowering plant taxa? Using an extensive pollen metabarcoding dataset from Canada, we discovered that honey bees may serve as dispersal agents for an array of sporophytes (Anchistea, Claytosmunda, Dryopteris, Osmunda, Osmundastrum, Equisetum) and bryophytes (Funaria, Orthotrichum, Sphagnum, Ulota). Our findings also suggest that honey bees may occasionally act as vectors for the dispersal of aquatic phototrophs, specifically Coccomyxa and Protosiphon, species of green algae. Our work has shed light on the broad resource‐access patterns that guide plant‐pollinator interactions and suggests that bees could act as vectors of gene flow, and potentially even agents of selection, across Plantae.